KARAKTERISTIK AKSEPTOR KB DAN PEMILIHAN CARA KONTRASEPSI DI PUSKESMAS DAGO BANDUNG TAHUN 2008 - Maya Safitri (Universitas Harapan Bangsa Purwokerto, 2008)
Objective : To know the acceptors characteristic and the most of contraception methodsused.Method : This study was descriptive with cross sectional approach. This study was donetoward all new acceptors of family planning at Dago Public Health Center Bandung inthe year of 2008.Result : The acceptors of family planning at Dago Public Health Center in the year of 2008 counted 352 acceptors. Based on the characteristic, the most acceptors were in20-30 years old : 58,2 % (205 acceptors), Parity 2-3 that were 44% (155 acceptors),the most education were junior high school 29,8% (105 acceptors) and work ashousewife 96,9% (341 acceptors). The most contraceptive method used was injectablecontraceptive : 81,5% (287 acceptors) and then oral contraceptive, intra uterincontraceptive device and implant.Conclusion : The most contraception acceptors were 20-30 years old, parity 2-3,education were junior high school and as housewife. The most contraceptive methodused was injectable contraceptive. Keywords : Contraception acceptors characteristic, contraceptive method.